Komparasi Usahatani Cabai Lahan Sawah Lereng Gunung Merapi dengan Lahan Pasir Pantai - Agus Dwi Nugroho; I Made Yoga Prasada; Saraswati Kirana Putri; Herdiana Anggrasari; Pinjung Nawang Sari (AGRARIS: Journal of Agribusiness and Rural Development Research, 2018)
The main production areas of chilli in Yogyakarta Province are in the wetland onthe slopes of Mount Merapi and in the sandy coastal area. This research was intended to compare the use of production inputs, technical efficiency and performance of chilli farming in both areas. The research was conducted in Pakem sub-district and Panjatan sub-district. The number of respondents in this research were 30 farmers in every sub-district. Descriptive analysis, frontier analysis and revenue-cost ratio were used in this research. The results indicated that the use of production inputs, production, technical efficiency, and performance of chilli farming in the sandy coastal area was higher than that in the wetland. The technical efficiency in the wetland on the slopes of Mount Merapi was determined by the quantity of counselling while in the sandy coastal area was determined by the quantity of counselling and farmers’ experience. The auction market in both areas proved able to increase the price of chilli. It is highly recommended that the extension officers need to be active in assisting farmers in both areas, especially related with chilli cultivation and processing technology.